Risk of gastrointestinal bleeding with direct oral anticoagulants: a systematic review and network meta-analysis. (February 2017) - Burr, Nick; Lummis, Katie; Sood, Ruchit; Kane, John Samuel; Corp, Aaron; Subramanian, Venkataraman
Summary: Background: Direct oral anticoagulants are increasingly used for a wide range of indications. However, data are conflicting about the risk of major gastrointestinal bleeding with these drugs. We compared the risk of gastrointestinal bleeding with direct oral anticoagulants, warfarin, and low-molecular-weight heparin. Methods: For this systematic review and meta-analysis, we searched MEDLINE and Embase from database inception to April 1, 2016, for prospective and retrospective studies that reported the risk of gastrointestinal bleeding with use of a direct oral anticoagulant compared with warfarin or low-molecular-weight heparin for all indications. We also searched the Cochrane Library for systematic reviews and assessment evaluations, the National Health Service (UK) Economic Evaluation Database, and ISI Web of Science for conference abstracts and proceedings (up to April 1, 2016). The primary outcome was the incidence of major gastrointestinal bleeding, with all gastrointestinal bleeding as a secondary outcome. We did a Bayesian network meta-analysis to produce incidence rate ratios (IRRs) with 95% credible intervals (CrIs). Findings: We identified 38 eligible articles, of which 31 were included in the primary analysis, including 287 692 patients exposed to 230 090 years of anticoagulant drugs. The risk of major gastrointestinal bleeding with direct oral anticoagulants did not differ from that with warfarin or low-molecular-weight heparin (factor Xa vs warfarin IRR 0·78 [95% CrI 0·47−1·08]; warfarin vs dabigatran 0·88 [0·59−1·36]; factor Xa vs low-molecular-weight heparin 1·02 [0·42−2·70]; and low-molecular-weight heparin vs dabigatran 0·67 [0·20−1·82]). In the secondary analysis, factor Xa inhibitors were associated with a reduced risk of all severities of gastrointestinal bleeding compared with warfarin (0·25 [0.07–0.76]) or dabigatran (0.24 [0.07–0.77]). Interpretation: Our findings show no increase in risk of major gastrointestinal bleeding with direct oral anticoagulants compared with warfarin or low-molecular-weight heparin. These findings support the continued use of direct oral anticoagulants. Funding: Leeds Teaching Hospitals Charitable Foundation.